100 ans de visions et lectures aériennes - André Humbert; Colette Renard-Grandmontagne (Bulletin de l’Association de Géographes Français)
Finally, the 20th century gave geographers the opportunity to rise above the surface of the earth to observe from a distance. While contemplating the earth from the top was an enchantment for the geographers of the beginning of the century who experienced and expressed it enthusiastically, it took a long time for them to make common use of it in their publications, which is shown, in particular, by a systematic review of the BAGF journal since its first issue. Today, oblique aerial photography is marginalized by more rigorous documents, but the oblique view, which retains the reality of landscapes, can bring much to the geographer, if put in such order as to highlight the spatial organization which is proposed in one single look.